ANALYSIS OF PREFERENCE RANKING ORGANIZATION METHOD FOR ENRICHMENT EVALUATION (PROMETHEE) AND SIMPLE MULTI ATTRIBUTE RATING TECNIQUE (SMART) TO CHOOSE COSMETICS APPROPRIATE TO SKIN TYPE - Jepri Banjarnahor; Junita Sari Ninggolan; Elekda Permata Sari Manurung; Kasa Lopian (Sean Institute, 2021)
Cleansing and moisturizing cosmetics are the most important part of facial skin care because they have benefits in maintaining healthy facial skin. More and more cleansing and acne products on the market make it difficult for consumers to choose which one suits their skin type. In this case, a cosmetic application is made by considering several available criteria and alternatives by applying the PROMETHEE and SMART methods and the running time of each selection method will be calculated. The selection system is very easy, by entering criteria according to skin type, price, age, texture and side effects as inputs in the selection, then we can find out which cleansers and preventions best suit the needs of the skin and the consumer's budget.